Hydrogen uptake and its influence in selective laser melted austenitic stainless steel: A nanoindentation study. (15th March 2021) - Park, Jeong-Min; Zhao, Yakai; Voisin, Thomas; Lee, Dong-Hyun; Komazaki, Shin-ichi; Ko, Yoonseok; Kim, Dong-Ik; Suh, Jin-Yoo; Han, Heung Nam; Wang, Y. Morris; Ramamurty, Upadrasta; Jang, Jae-il
Abstract: The effect of hydrogen (H) charging on the nanoindentation response of a selective laser melted (SLM) 316L austenitic stainless steel was investigated and compared with its conventionally manufactured (CM) counterpart. Results show that the hardness increment in the SLM samples due to H charging is relatively smaller. Thermal desorption spectroscopy analysis suggests that the charged SLM alloy has not only a smaller H content but a lower apparent H diffusivity in comparison to the CM alloy. This was attributed to the ultrafine solidification cell structure in the SLM alloy. Through the low-load nanoindentation experiments and forward-scattered electron imaging analysis, statistical distributions of the hardness of the cell walls and interiors were assessed. The cell walls, consisting of high-density dislocations with segregated elements, were relatively insensitive to H charging than the cell interiors. These results are discussed in terms of the apparent H solubility and diffusivity in the SLM alloy. Graphical abstract: Image, graphical abstract